PandoraHearts. 22 - Mochizuki, Jun (Yen Press, 2014)
Where in the world are you? This question is posed to Oz Vessalius once more. After overcoming the chains of infinite despair that bind him, the answer at which he arrives becomes a blinding light, piercing through the jet-black darkness. As though hope can be spun out of the emotions of a person's heart ...